Kepala Sekolah sebagai Leadership dalam Menuju Good Governance Disiplin Guru dan Karyawan - Desy Wulandari; Yayuk Fauziah (LP2M STIT Palapa Nusantara, 2019)
Principal's leadership is a model of leadership that is implemented based on certain situations and conditions in influencing, directing and improving the performance of his subordinates by strengthening enthusiasm and motivation and rewards. This research aims to study the principal’s strategy in improving teacher and employee discipline. This study uses a descriptive-qualitative method with the subject of the research as head, curriculum waka and the teacher council. Data is collected by interview, observation and documentation. The results showed that the efforts of principals in improving teacher and employee discipline had been carried out correctly, effectively, efficiently so as to improve the discipline of teachers and employees.